Expert System of Early Detection of Diseases by Blood Type Using Backward Chaining Method - Sarini Vita Dewi; Fauziah Fauziah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Expert System Application Design To Detect Disease Based on Android Based Blood Group Using Backward Chaining Method Expert system application design to detect disease based on android based blood group using bakcward chaining method has been successfully done. This expert system application is designed to generate information, so that people can understand the various diseases based on blood type and can make early prevention of the disease and can be used anytime so it is more efficient with time. The design of this expert system application consists of several software that is used, such as: Android Studio that works for android application development. Java serves as a java programming language used in a designed application, and PostgreSQL Database as a means of storing data in the server computer. The test results that have been done on expert system application to detect disease based on android based blood group using bakcward chaining method is expert system application program can solve the problem that can display the diagnosis result quickly and precisely based on the symptoms entered by User.Keywords: Expert System, Android, Backward Chaining, Blood type